The Risk of Venous Thromboembolism Events Resulting in Hospitalization following Exposure to Antipsychotic Medication in Pre-Disposed Adult Patients - Rachel Kahle; Laura Sjoquist; Lindsey Peters (INNOVATIONS in Pharmacy, 2024)
Introduction:  The primary objective of this study was to compare the incidence of antipsychotic use in those with venous thromboembolism (VTE) resulting in hospital admission. This study expands upon current knowledge regarding VTE risk and antipsychotic use and investigates potential risk factors and lab values that may precede antipsychotic-induced coagulopathy.